2013
DOI: 10.1364/oe.21.025677
|View full text |Cite
|
Sign up to set email alerts
|

Grating-based x-ray phase-contrast imaging with a multi energy-channel photon-counting pixel detector

Abstract: Abstract:We have carried out grating-based x-ray differential phasecontrast measurements with a hybrid pixel detector in 16 energy channels simultaneously. A method for combining the energy resolved phase-contrast images based on energy weighting is presented. An improvement in contrast-to-noise ratio by 58.2% with respect to an emulated integrating detector could be observed in the final image. The same image quality could thus be achieved with this detector and with energy weighting at 60.0% reduced dose com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Furthermore, energy resolved detection, [25][26][27] as supported by the next generation MicroDose system, can further improve the SNR. [28][29][30] Since our ultimate goal is phase-contrast mammography, future work will also include the imaging of breast samples.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, energy resolved detection, [25][26][27] as supported by the next generation MicroDose system, can further improve the SNR. [28][29][30] Since our ultimate goal is phase-contrast mammography, future work will also include the imaging of breast samples.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal k of −0.77 is not a very strong weight. In comparison, weighting factors proportional to E −3 are found in attenuation imaging [17,18] and proportional to E −2 for phase-contrast imaging [21]. Also in this measurement the index of k = −0.77 had to be determined iteratively.…”
Section: Discussionmentioning
confidence: 99%
“…In previous publications, Talbot-Lau interferometers were combined with energy-resolving x-ray detectors for phase-contrast imaging only. It was shown that artifacts can be removed [19] and that the image quality can be improved by setting optimized energy thresholds [20] or by appropriate energy-weighting [21]. Here, we evaluate the benefit of an energy-resolving detector in x-ray dark-field imaging.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of small variances with σ 2 w 1.3 it has been shown [32], [33], that the concentration κ w can be approximated with 1…”
Section: B Maximum Likelihood Estimation Of the Unwrapped Phasementioning
confidence: 99%
“…With regularization (continuous curve) a preference is added for small values of ϕ * which leads to an estimated value ofφ * reg = −1.9 rad. In view of other related work, in particular the work by Pelzer et al [33] on optimal energy weighting of spectral phase contrast data, it is also instructive to investigate the case where the variances σ 2 w = κ −1 w are small and the true phase shifts are so small that no phase wrapping occurs. In this limiting case, we can drop the regularization and (12b) becomes a weighted least square optimization problem.…”
Section: B1 Regularizationmentioning
confidence: 99%